Relevansi Tata Kelola Wakaf Turki terhadap Pengembangan Wakaf Produktif di Indonesia - Yusi Septa Prasetia; Miftahul Huda (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
This paper describes the profile of productive waqf management developed in Turkey and tries to relate certain aspects in the context of waqf development in Indonesia. Waqf management in Turkey in terms of history, legal formation, and asset management, especially productive waqf assets, has grown rapidly and at least contributed to the state and the empowerment and independence of the community. The institutional, governance, and distribution of waqf proceeds have had major implications for the Turkish state. At least by positioning waqf assets to be developed productively, it has strengthened the function of waqf in the transformation of Muslims specifically. In this context, it is possible that the efforts that have been made by Turkish waqf in terms of asset productivity are taken more integratively for the development of waqf in Indonesia.